The prince - Machiavelli, Niccolo (London HarperCollins, 2011)
HarperCollins is proud to present its new range of best-loved, essential classics. 'We have declared before that it is not only expedient but necessary for a prince to take care his foundations be good, otherwise his fabric will be sure to fail.' Considered one of the first works of modern philosophy, Machiavelli's The Prince is an intense study on the nature of power and the course it should take when ruling a country and expresses the author's strong and unyielding ideals and beliefs on using force rather than law to achieve your aims. Responsible for the widely-used phrase 'Machiavellian', with all of its negative connotations, his extreme treatise remains a classic text to this day.